SPEECH ACTS IN JULIA GILLARD™S SPEECHES - Purwadi, Dede; Sihombing, Lince (Universitas Negeri Medan, 2013)
ABSTRACTThis study is concerned with pragmatics, focusing on the types of speech acts used in Julia Gillard™s Speeches. This research was conducted by using qualitative descriptive design. There are four textŸs speeches of Julia Gillard in this study taken from internet, There were 241 utterances. The results of data analysis showed the total numbers were: declarative 3,7%, representative 52,7%, expressive 6,2%, directive 12,0%, commissive 25,3%. It means that representative form is the most dominant type of speech acts used in Julia GillardŸs speeches. It is 52,7%. Representative is dominant because the speaker who delivered the speech is only person who becomes the center of attention and they are campaign or political speeches. Usually, the speakers would promote about their self and talk about their potency to be a good leader with all their goals to convince the hearer.Keywords: Pragmatics, Speech Acts, Political Speech